Synthesis, and Docking Studies of Some Fused-quinazolines and Quinazolines Carrying Biological Active Isatin Moiety as Cell-cycle Inhibitors of Breast Cancer Cell Lines - Radwan, A. A.; Alanazi, F. K.; Al-Dhfyan, A. (Drug Research, 2013)
3 series of novel fused heterocyclic systems, viz. triazolo[4,3-a]quinazolin-7-ones (3), 1245-tetrazino[4,3-a]-quinazolin-8-ones (5) and Schiff’s bases of isatin derivatives with 2-hydrazinoquinazolin-4-ones (7) have been synthesized. Several of them showed variable and promising in vitro antiproliferative activity against the MCF-7 cells. Compounds 3a-3c, 6, 7a-7 f showed promising activity (IC50=12.45–15.79 μM). Compound 7 f possessed notable cell cycle disrupting and apoptotic activities with enhanced selectivity against cancer cells, suggesting the potential for the development of new selective cell cycle inhibitors. In silico docking study of the compound 7 f with EGFR enzyme postulated that the designed compound might act on the same enzyme target where DJK_3021_A x-ray structure acted.
Keywords: quinazolinones; EGFR; antiproliferative; MCF-7; Dock6.2